The Palace Architecture of the Roma Population in Romania - Preda, Mihaela-Daniela; Vijulie, Iuliana; Lequeux-Dincă, Ana Irina (Eastern European Countryside, 2024)
Contrasting the local specific architecture through an obvious opulent style, “palaces” of Roma population in Romania generate controversial debates. The present study analyses this phenomenon from a socio-geographic perspective in its attempt to draw attention to the new constructions appearing in the post- communist period after 1990. The Roma palaces are a choice of a showy non- constrained way to manifest an ethnic socio-economic status at the local level are perceived differently in Romanian society by the Roma community and by the Romanian population respectively. Our research methodology was correlated with the particularities of this topic and has been very infrequently approached until the present moment. It has hence used as its main tools direct observation, a social survey based on semi-structured interviews and media monitoring. The results of the study have mainly showed that the appearance of the new type of residences is a consequence of the change in the socio-economic statute of the Roma population, the size of the house being directly proportional to the status of the privileged within a community. Moreover, we have already witnessed architectural trends in the aesthetics of these constructions, which were mainly perceived in a negative way by the Romanian respondents and in a positive way by Roma respondents.